Donor‐Site‐Directed Rational Assembly of Heteroleptic cis‐[Pd2L2L′2] Coordination Cages from Picolyl Ligands. Issue 49 (30th July 2018) - Zhu, Rongmei; Bloch, Witold M.; Holstein, Julian J.; Mandal, Soham; Schäfer, Lars V.; Clever, Guido H.
Abstract: A donor‐site engineering approach facilitates the formation of heteroleptic [Pd2 L 2 L ′2 ] 4+ cage structures through a favored cis ‐′in2 /out2 ′ spatial configuration of the methyl groups of 5‐ and 3‐substituted bis‐monodentate picolyl ligands with flat acridone and bent phenothiazine backbones. The heteroleptic cages were confirmed by ESI‐MS and 2D NMR experiments as well as DFT calculations, which pointed toward a cis ‐configuration being energetically favored. This was further supported by the synthesis and X‐ray structure of a previously unreported cis ‐[Pd(2‐picoline)4 ] 2+ complex. The formation of homoleptic structures, however, was met with considerable steric hindrance at the Pd II centers, as observed by the formation of [Pd2 L 3 (solvent)2 ] 4+ and [Pd2 L 2 (solvent)4 ] 4+ species when only one type of acridone‐based ligand was offered. In contrast, bent phenothiazine ligands with outside‐pointing methyl groups showed the ability to form interpenetrated double‐cages, as revealed by X‐ray crystallography. The general route presented herein enables the assembly of uniform cis ‐[Pd2 L 2 L ′2 ] 4+ coordination cages, thus furthering the possibility to increase structural and functional complexity in supramolecular systems. Abstract : Two in, two out : An energetically favorable orientation of picoline donors facilitates the selective formation of heteroleptic cis ‐[Pd2 L 2 L ′2 ] cages. Whilst this general approach alleviates steric crowding to enable heteroleptic cage structures, homoleptic self‐assembly results in [Pd2 L 3 (solvent)2 ] bowls, [Pd2 L 2 (solvent)4 ] rings and in certain cases in [Pd4 L 8 ] double‐cages.